Microwave Assisted Green Synthesis of Ag, Ag2O, and Ag2O3 Nanoparticles - Korkmaz, Nesrin; Karadağ, Ahmet (Turkish Chemical Society, 2021)
In this study, nanoparticles containing Ag, Ag2O, and Ag2O3 mixture were synthesized by using a microwave-assisted green synthesis method. For the reduction of Ag+ to Ag0, Rhododendron ponticum plant extract was used while the microwave synthesis method was used for the formation of silver oxides. Nanoparticles synthesized under 90 °C, 450 W, and 30-minute microwave synthesis conditions were characterized by UV-Vis, XRD, and STEM. As a result of characterization, Ag-NPs were found to show maximum absorbance peak at 432 nm in the UV-Vis spectrum, crystallite size was 46 nm according to XRD analysis, and nanoparticles showed in a spherical homogeneous distribution by STEM analysis. Our results showed that the phytochemicals in the plant extract of R. ponticum reduce Ag+ ions to Ag-NPs and that the mixture of silver and silver oxide can be synthesized quickly and easily with microwave heating support. This study is important to increase the use of Ag2O and Ag2O3 nanoparticles in industrial production and medical applications. In particular, nanoparticles of silver and silver(I) oxide show great promise for widespread usage in medical polymers and nanodrugs. Because in this study, toxic chemicals were not used in the synthesis of silver oxide nanoparticles and it is a safe synthesis because there is no risk of explosion.